Rapidly hydrolyzable polylactide resin composition

JP7638229B2Active Publication Date: 2025-03-03NATUREWORKS LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021571662
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-13
Filing Date
2020-05-25
Publication Date
2025-03-03
Estimated Expiration
2040-05-25

AI Technical Summary

Benefits of technology

は、出発ポリラクチド樹脂組成物の質量の少なくとも75%、少なくとも80%、少なくとも85%、又は少なくとも90%が失われるまで、このプラトーに達しない場合が多いことである。それに対応して、残留物は、ポリラクチド樹脂組成物の出発重量の25%以下、20%以下、15%以下、又は10%以下でさえある場合が多い。時間及び十分な濃度の水を付与すると、これらの微結晶はさらに加水分解し、最終的に加水分解媒体に溶解し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638229000009
    Figure 0007638229000009
  • Figure 0007638229000010
    Figure 0007638229000010
  • Figure 0007638229000001
    Figure 0007638229000001
Patent Text Reader

Abstract

A polylactide resin composition that exhibits a fast hydrolysis rate and leaves a low residual amount includes poly(meso-lactide) and a second polylactide, and is useful in applications where rapid hydrolysis at low to moderately high temperatures is desirable, such as certain oil and gas well treatment applications.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polylactide resin composition that rapidly hydrolyzes in aqueous media.

[0002] Polylactide resins are known to hydrolyze in the presence of water. Given sufficient time, polylactide resins can eventually hydrolyze to form lower molecular weight species that are soluble in water or can be consumed by microorganisms. This ability to hydrolyze makes polylactide resins compostable. [Background technology]

[0003] Some applications of polylactide have sought to take advantage of this property. One such application is as a degradable chemical diverter in oil and / or gas producing wells. Diverters are used in injection processes to ensure uniform distribution of treatment fluids across the treatment interval. Injected fluids tend to follow the path of least resistance, potentially resulting in areas of least permeability that undergo improper treatment. Diverters are injected into the formation with the treatment fluid. When installed, the diverter temporarily blocks certain areas of the formation from the injection process, diverting the process to areas of low permeability that may not otherwise be properly treated. To be effective, the diversion must be temporary so that full production of the well can be maintained when the process is completed. Polylactide resin provides the required temporary blocking action, as low molecular weight species are formed that hydrolyze and dissolve or are washed away under the moisture and temperature conditions in the well, resulting in the blocked areas of the formation reopening when the well goes into production.

[0004] The problem is that hydrolysis proceeds slower than desired, causing the diverter to remain in place for too long. This problem is particularly acute in low temperature formations (such as 37-66 °C).

[0005] Polylactide hydrolysis rates are related to the degree of crystallinity. Highly crystalline polylactides tend to hydrolyze relatively slowly. For this reason, so-called "amorphous" polylactide grades have been preferred when faster hydrolysis rates are desired. "Amorphous" polylactide grades are polylactide resins that are difficult to crystallize, and if they do crystallize, they produce only a small number of crystallites that have a lower melting point than more easily crystallized polylactide resins.

[0006] In general, the ability of a polylactide resin to crystallize strongly depends on its stereochemistry. Commercially available polylactide resins are almost always copolymers containing randomly distributed L-(S) and D-(R) lactic acid units. Higher stereochemical purity correlates with a higher ability to crystallize. So-called "amorphous" grades may contain as much as 80-92% of the predominant enantiomer (usually the L-lactic acid enantiomer in commercial grades) and 8-20% of the other enantiomer. A specific example of a polylactide resin used in diverter applications is a random copolymer of L-lactide, meso-lactide, and optionally D-lactide, containing 12% D-lactic acid units.

[0007] Even some commercially available amorphous grades have been found to hydrolyze too slowly under some well conditions.

[0008] Polylactide diverters should have other important properties. These diverters are in the form of a mixture of particles, i.e. small pellets, powders, fibers, and / or flakes, in different weight ratios and sometimes with different densities. The particles should be resistant to agglomeration or "blocking" under dry conditions (i.e., in the absence of moisture or liquid water), so that they can be transported and stored without the need for climate-controlled containers to mitigate the formation of agglomerates. Because the diverters are stored on-site under ambient conditions, they should be resistant to blocking when stored at temperatures as high as 45°C or 50°C, which are sometimes encountered in hot summer climates in oil and gas producing basins such as the Permian in West Texas. Unfortunately, highly amorphous polylactide resins, which tend to hydrolyze quickly, also tend to block easily. Thus, improvements to polylactide resins that favor faster hydrolysis and mass loss also tend to promote blocking.

[0009] Additionally, the way the polylactide diverter behaves during transfer downhole is important. The diverter should not hydrolyze too quickly as large cohesive, sticky masses will form as the diverter is transported to the fracture where diversion is desired. Migration of sticky hydrolysis residues to the surface as the well goes into production can cause fouling of the production equipment surfaces. In preferred systems, the diverter particles do not agglomerate or only form a mass of lightly cohesive particles that can be easily broken down mechanically at the surface when they are mixed with water and pumped downhole.

[0010] Yet another important characteristic is the degree of mass loss the diverter particles undergo. The amorphous phase in PLA is known to hydrolyze much more rapidly than the crystalline phase. Even amorphous PLA grades are also known to develop some level of crystallinity during hydrolysis, especially if the hydrolysis is carried out at temperatures below 110°C. Under these temperature conditions, hydrolysis of the amorphous phase and solubilization of the oligomeric products prevails over the crystalline phase, at which point a pronounced plateau is reached and further mass loss becomes very slow. Once this plateau is reached, the remaining mass (sometimes called "residue") should be as small as possible, preferably no more than 25% of the original diverter mass. In addition to hydrolyzing too slowly for some applications, polylactide resins used in diverter applications tend to have more "residue" than is desired, i.e., the rate of mass loss becomes very slow if as much as 50-60% of the original diverter mass remains. Residue tends to be more often observed when hydrolysis is carried out at lower temperatures (≦66°C) rather than higher temperatures.

[0011] It would be desirable to have a polylactide resin composition that hydrolyzes rapidly and produces small amounts of residue, particularly at temperatures between 37-66° C. It would be even more desirable if such compositions were resistant to blocking under dry conditions, particularly at moderately elevated temperatures such as 40-50° C. The compositions preferably are resistant to blocking when in the wet state at similar temperatures. Summary of the Invention [Means for solving the problem]

[0012] The present invention relates to a) 50 to 95% by weight, based on the weight of all polylactides in the composition, of at least one polymer or copolymer of meso-lactide having a number average molecular weight of at least 5000 g / mol, as measured by gel permeation chromatography (GPC) against polystyrene standards, which polymer or copolymer contains at least 90% by weight of lactic acid units, at least 80% of which are formed by polymerization of meso-lactide, and has an average length of the blocks of L-lactic acid and D-lactic acid units of at least 1.1 to 2.0; b) A polylactide resin composition comprising a melt or solution blend of 5-50% by weight, based on the weight of all polylactides in the composition, of at least one polylactide having a number average molecular weight of at least 5000 g / mol, as measured by GPC against polystyrene standards, and at least 90% by weight of lactic units containing L-lactic and D-lactic units in a ratio of ≧65:35 or ≦35:65.

[0013] For convenience, the above-mentioned polymers or copolymers of lactide will be referred to herein as "poly(meso-lactide)" or "PMLA", and the aforementioned polylactide in paragraph b) above will be referred to as "polylactide (b)".

[0014] The polylactide resin composition of the present invention offers several surprising and even important advantages. It exhibits a fast rate of hydrolysis, even at moderate temperatures, such as 37-66°C, compared to commercially available polylactide resin grades. The fast rate of hydrolysis is a major advantage in industrial composting and in certain end uses, such as when the composition is used as a diverter in oil and / or gas producing wells. This fast rate of hydrolysis continues until most of the original volume of the composition has been lost, leaving little "residue."

[0015] Moreover, the rate of hydrolysis is "tunable" over a wide range by varying the ratio of PMLA and polylactide (b), as well as by including or excluding (and varying the amounts, if present) various additives, as described more fully below.

[0016] The polylactide resin composition of the present invention is resistant to blocking under dry conditions up to moderately high temperatures, such as 40 to 50°C.

[0017] Furthermore, the agglomerates of particles of the polylactide resin composition tend to hydrolyze (and lose mass due to such hydrolysis) in a particularly beneficial manner, especially when hydrolyzed at low or moderate temperatures (such as below 100°C). As hydrolysis proceeds, the particles tend to maintain their granular nature without blocking or agglomerating into sticky masses. As described below, such agglomerates of particles may form light agglomerates during intermediate stages of hydrolysis, but the particles largely maintain their granular identity throughout. As more mass is lost, the remaining portions of the particles tend to develop significant amounts of crystallinity, at which point they once again become discreet and non-agglomerated, or nearly so. The molecular weight of such crystalline residues is generally quite low, usually less than 5000 g / mole (measured by GPC against polystyrene standards), and therefore have little mechanical strength and are brittle. In diverter applications, this allows the residue to be easily removed from the formation without affecting permeability retention, reducing fouling of the equipment at the well surface. It is surprising that PMLA would produce any significant degree of crystallinity by itself, since PMLA is generally not amenable to crystallization, and polylactide (b) may be a grade that crystallizes only to a small extent by itself, if at all.

[0018] These properties make the polylactide compositions of the invention particularly well adapted for use as diverters in subterranean formations. Accordingly, in another aspect, the invention provides a method of treating a subterranean formation, comprising the steps of: a) introducing a treatment fluid containing a liquid phase and particles of the polylactide composition of the first aspect into a subsurface formation such that a mass of the particles is deposited in the subsurface formation; and then b) hydrolyzing the deposited particles in the subsurface formation by subjecting the deposited particles to an aqueous medium and elevated temperature such that the deposited particles lose at least 50% of their starting mass due to hydrolysis; The method includes: [Brief description of the drawings]

[0019] [Figure 1] 1 is a graph illustrating the mass loss of the polylactide resin composition of Example 1. [Diagram 2] 1 is a graph illustrating the mass loss of the polylactide resin composition of Example 13. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] PMLA Lactic acid is a molecule with one chiral center and therefore exists in two enantiomeric forms: the so-called D- (or R-) enantiomer and the L- (or S-) enantiomer. Two molecules of lactic acid can be condensed with the elimination of two molecules of water to form 3,6-dimethyl-1,4-dioxane-2,5-dione, referred to herein as "lactide." Lactides each have the following structure: [ka] It can be thought of as consisting of two "lactic acid units" having the following structure:

[0021] Each lactic acid unit in a lactide molecule contains one chiral center and exists in either the D or L configuration. Lactide molecules can be in one of two forms: 3S,6S-3,6-dimethyl-1,4-dioxane-2,5-dione (L-lactide), 3R,6R-3,6-dimethyl-1,4-dioxane-2,5-dione (D-lactide), and 3R,6S-dimethyl-1,4-dioxane-2,5-dione (meso-lactide). These have the following structures: [ka]

[0022] L-lactide and D-lactide are a pair of enantiomers, and meso-lactide is a stereoisomer with one L-lactic acid unit and one D-lactic acid unit. Furthermore, a mixture of about 50% L-lactide and 50% D-lactide forms a high melting point material known as racemic-lactide (or "rac-lactide"). Hydrolysis of both meso-lactide and rac-lactide can yield a mixture of 50% L-lactic acid and 50% D-lactic acid.

[0023] Meso-lactide is unique among the various forms of lactide because when it is homopolymerized, the number of consecutive L-lactic and D-lactic units produced in the polymer can be as low as one or as high as two. Polymerization of a mixture of L-lactide and D-lactide will incorporate segments of an even number of lactic units in the polymer, the average block length of which can be determined by the ratio of the monomers present in the feedstock. When added to the end of a growing polymer during the polymerization process, a molecule of meso-lactide will introduce a single L-lactic and a single D-lactic unit at its chain end. When meso-lactide is polymerized in a "head-to-tail" fashion (i.e., a D-lactic unit is added to a terminal L-lactic unit on the polymer chain, or vice versa), the following form can be obtained: (DLDL) n where D represents the D-lactic acid units and L represents the L-lactic acid units. PMLA with this configuration is sometimes called "syndiotactic". In this configuration, the number of consecutive D- and L-lactic acid units is always 1. Conversely, when meso-lactide is polymerized in a "head to head" fashion (i.e., when a D-lactic acid unit is added to a terminal L-lactic acid unit), the following form is produced: (DLLD) n Instead, a polymer with the structure is produced. PMLA with this structure is sometimes called "heterotactic". In this case, the number of consecutive D- and L-lactic acid units is always 2. When meso-lactide is polymerized randomly, the number of consecutive D- and L-lactic acid units is sometimes 1, sometimes 2, with an average value of 1-2.

[0024] The PMLA of the present invention is a homopolymer of meso-lactide, or a copolymer of at least 80% meso-lactide and up to 20% lactide, preferably at least 88% meso-lactide and up to 12% other lactides, or at least 90% meso-lactide and up to 10% other lactides. If a copolymer, then the copolymer may be a random and / or block copolymer. The other lactide may be any other lactide, including L-lactide, D-lactide, or rac-lactide, or a mixture of any two or more thereof.

[0025] At least 90% or at least 95% by weight of PMLA is composed of lactic acid units, of which 40-60% are L-lactic acid units and correspondingly 60-40% are D-lactic acid units.

[0026] PMLA may further contain repeat units formed from other monomers copolymerizable with lactide, such as alkylene oxides (including ethylene oxide, propylene oxide, butylene oxide, tetramethylene oxide, etc.), cyclic lactones, or carbonates. The repeat units derived from these other monomers may be present in block and / or random configurations. These other repeat units suitably constitute up to 10% by weight of the polylactide, preferably 0-5% by weight, especially about 0-2% by weight, or may be absent.

[0027] PMLA may also contain residues of initiator compounds, which are often used during polymerization processes to provide molecular weight control.Suitable such initiators include, for example, water, alcohols, various types of polyhydroxy compounds (such as ethylene glycol, propylene glycol, polyethylene glycol, polypropylene glycol, other glycol ethers, glycerin, trimethylolpropane, pentaerythritol, hydroxyl-terminated butadiene polymers, etc.), polycarboxy-containing compounds, and compounds having at least one carboxyl and one hydroxyl group (such as lactic acid or lactic acid oligomers).Except when the initiator is a residue of lactic acid or lactic acid oligomers, which may constitute any proportion relative to PMLA, the initiator residues preferably constitute no more than 5% by weight of PMLA, in particular no more than 2%.

[0028] PMLA may have long chain branches (having 3 or more carbon atoms). Long chain branches can be introduced into the polylactide in a variety of ways, such as by reacting epoxide groups present on the acrylate polymer or copolymer with carboxyl groups on the polylactide. The acrylate polymer or copolymer is characterized as containing an average of about 2 to about 15 free epoxide groups / molecule (e.g., about 3 to about 10 or about 4 to about 8 free epoxide groups / molecule), being solid at 23° C., and being the polymerization product of at least one epoxy-functional acrylate or methacrylate monomer, preferably copolymerized with at least one additional monomer. The acrylate polymer or copolymer suitably has a number average molecular weight of about 150 to about 700, such as 200 to 500 or 200 to 400 g / mol, per epoxide group. The acrylate polymer or copolymer suitably has a number average molecular weight of 1000 to 6000, such as about 1500 to 5000 or about 1800 to 3000 g / mol. Other approaches to introduce long chain branching are described in US Patent Nos. 5,359,026 and 7,015,302, and WO 06 / 002372 A2.

[0029] In a preferred embodiment, the PMLA lacks long chain branching.

[0030] The number average molecular weight of PMLA, measured by GPC against polystyrene standards, may range, for example, from 5000 to 200,000 g / mol. Number average molecular weights of about 30,000 to 130,000 g / mol are preferred.

[0031] In some embodiments, the PMLA is characterized by having a relative viscosity of 1.1-6, 1.25-5, or 1.5-3.5, measured in a capillary viscometer at 30° C. using 1% (wt / vol) polylactide resin in chloroform against a chloroform standard.

[0032] PMLA can be heterotactic, or partly syndiotactic and partly heterotactic. The average length of the blocks of L-lactic and D-lactic units in PMLA can be, for example, equal to at least 1.1, at least 1.2, at least 1.25, or at least 1.3, for example up to 2, up to 1.75, up to 1.5, or up to 1.4. The average block length can be determined by the method of determining pm as described by Coates et al., J. American Chemical Society 2002, 124, 1316, and the following relationship: Average block length = 1 + P m / (1+(1-P m )) can be determined by proton NMR using

[0033] In some embodiments, the PMLA has a glass transition temperature of 38-50°C.

[0034] The PMLA is characterized as being an amorphous PLA grade. By "amorphous grade" it is meant that the PMLA contains 5 J / g or less crystallites after heating at 110°C for 1 hour in air. The sample is preheated to at least 220°C to melt the crystallites and then quenched by rapidly cooling to room temperature (23±3°C). The quenched sample is then heated to 110°C for 1 hour and quenched again by cooling to room temperature. The crystallinity is then measured, conveniently using differential scanning calorimetry (DSC) method. The amount of such crystallinity is expressed herein in J / g, i.e., the enthalpy of fusion (joules) of the polylactide crystals in the sample divided by the weight (grams) of polylactide in the sample. A convenient test protocol for performing DSC measurements is to heat 5-10 milligrams of sample from 25°C to 225°C at 20°C / min under air on a Mettler Toledo DSC3+ calorimeter, or equivalent, implemented with STARe V.16 software.

[0035] PMLA is produced by polymerizing meso-lactide with itself or by copolymerizing it with other lactides in a random and / or block fashion. The polymerization can be carried out batchwise, semi-continuous, or continuous.

[0036] Suitable polymerization temperatures are preferably above the melting temperature of the monomer or monomer mixture below which significant polymer degradation occurs. The temperature range can be, for example, as low as 60°C or as high as 225°C.

[0037] Molecular weight and conversion are controlled by polymerization time and temperature, the equilibrium between free lactide and polymer, and by the use of initiator compounds. In general, increasing the amount of initiator compounds on a molar basis tends to decrease the molecular weight of the product polymer. Molecular weight control agents can also be added to obtain the desired molecular weight, as described in U.S. Patent No. 6,277,951.

[0038] It is preferred to carry out the polymerization in the presence of a polymerization catalyst. Examples of these catalysts include various tin compounds, such as SnCl 2 , SnBr 2 , SnCl 4 , SnBr 4 , SnO, tin(II) bis(2-ethylhexanoate), butyltin tris(2-ethylhexanoate), hydrated monobutyltin oxide, dibutyltin dilaurate, tetraphenyltin, etc.; PbO, compounds such as zinc alkoxides, zinc stearate, aluminum alkoxides, compounds such as antimony triacetate and antimony(2-ethylhexanoate), compounds such as bismuth(2-ethylhexanoate), calcium stearate, magnesium stearate, certain yttrium and rare earth compounds as described in U.S. Pat. No. 5,208,667 to McLain et al., chiral (R)-(SalBinap)-AlOCH as described in Macromol. Chem. Phys. 1996, 197, 2627-2637, 3complexes, single-site β-diimidate zinc alkoxide catalysts as described in JACS 1999, 121, 11583-11584, lithium t-butoxide aggregates as described in Macromolecules 1995, 28, 3937-3939 and Polymer 1999, 40, 5455-5458; aluminum and yttrium-based catalyst complexes as described in JACS 2002, 124, 1316-1326, dinuclear indium catalysts as described in Macromolecules 2016, 49, 909-919, etc. The catalyst is used in a catalytically effective amount which depends somewhat on the particular catalyst, but is typically used in the range of 1 mole of catalyst per 3000-50,000 moles of monomer.

[0039] The selection of catalyst and polymerization temperature can each affect the stereochemistry of PMLA. In general, it has been found that the selection of higher polymerization temperatures, especially 120°C or higher, especially 150°C or higher, reduces stereospecificity in PMLA, resulting in average block lengths greater than 1 and less than 2. Similarly, tin-based catalysts also tend to reduce stereospecificity. In some embodiments, PMLA is polymerized using tin catalysts at temperatures of at least 120°C, preferably at least 150°C, up to 225°C, more preferably up to 190°C.

[0040] The resulting PMLA resin contains metal catalyst residues, which are preferably deactivated by contacting the PMLA resin with a deactivating agent.

[0041] The residence time under polymerization conditions is selected to produce a polymer of the desired molecular weight and / or desired conversion of monomers.

[0042] PMLA may contain residual lactide. If present, lactide may constitute up to 20%, up to 15%, up to 10%, up to 5%, or up to 2% by weight of the PMLA.

[0043] Polylactide (b) The polylactide (b) has a number average molecular weight of at least 5000 g / mol, measured by GPC against polystyrene standards. The number average molecular weight can be, for example, up to 200,000 g / mol. As with PMLA, a number average molecular weight of about 30,000 to 130,000 g / mol is preferred.

[0044] Polylactide (b) is, in some embodiments, characterized in that it has a relative viscosity of 1.1 to 6, e.g., 1.25 to 5, or 1.5 to 3.5, measured in a capillary viscometer at 30° C. using 1% (weight / volume) polylactide resin in chloroform against a chloroform standard.

[0045] The lactic acid units constitute at least 90% by weight or at least 95% by weight of polylactide (b). As with PMLA, the remaining weight of polylactide (b), if any, may include residues of initiator compounds and / or repeat units produced by polymerizing one or more monomers different from lactide.

[0046] The lactic acid units in polylactide (b) consist of L-lactic acid units and D-lactic acid units in a ratio of ≧65:35 or ≦35:65. This ratio can be, for example, 75:25 to 100:0, 80:20 to 100:0, 85:15 to 100:0, 86:14 to 100:0, 25:75 to 0:100, 20:80 to 0:100, 15:85 to 0:100, or 14:86 to 0:100. It is preferred that the L-lactic acid units and the D-lactic acid units are randomly arranged.

[0047] In some embodiments, the polylactide (b) is a semi-crystalline grade and has a ratio of L-lactic acid units to D-lactic acid units of 92:8 to 100:0 or 8:92 to 0:100.

[0048] In another embodiment, the polylactide (b) is of amorphous grade and the ratio of L-lactic acid units to D-lactic acid units is 86:14 to 92:8 or 8:92 to 14:86.

[0049] Polylactide (b) in some embodiments is a homopolymer of L-lactide or a random copolymer of L-lactide with one or more of meso-lactide, D-lactide, and rac-lactide. In the latter case, the ratio of the various lactides is selected to obtain a ratio of L-lactic acid units to D-lactic acid units of 65:35 to 99.9:0.1. This ratio is in some embodiments 75:25 to 99.9:0.1, 80:20 to 99.9:0.1, 86:14 to 99.9:0.1, 92:8 to 99.9:0.1, or 86:14 to 92:8.

[0050] Polylactide (b) in some embodiments is a homopolymer of D-lactide or a random copolymer of D-lactide with one or more of meso-lactide, L-lactide, and rac-lactide. In the latter case, the ratio of the various lactides is selected to obtain a ratio of L-lactic acid units to D-lactic acid units of 35:65 to 0.1:99.9. This ratio is in some embodiments 25:75 to 0.1:99.9, 20:80 to 0.1:99.9, 14:86 to 0.1:99.9, 8:92 to 0.1:99.9, or 15:85 to 8:92.

[0051] Polylactide (b) preferably does not contain both a polylactide having an L-lactic acid unit:D-lactic acid unit ratio of 65:35 or more and another polylactide having an L-lactic acid unit:D-lactic acid unit ratio of 35:65 or less.

[0052] Polylactide (b) in some embodiments has a glass transition temperature of 55-65°C and a crystalline melting temperature (if semi-crystalline) of 95-195°C.

[0053] Other properties of polylactide (b) and the manner in which it is produced are as described above for PMLA.

[0054] Polylactide resin composition The polylactide resin composition comprises a mixture of polylactide resins. The polylactide resin is a melt or solution blend, rather than a physical mixture of separate particles of the constituent polylactides. PMLA comprises 50-95% by weight of the total weight of all polylactides. In some embodiments, PMLA comprises at least 60%, at least 65%, or at least 70% by weight of the total weight of all polylactides. In some embodiments, PMLA comprises up to 90%, up to 85%, or up to 80% of all polylactides.

[0055] Polylactide (b) comprises 5-50% by weight of the total weight of all polylactides. In some embodiments, polylactide (b) comprises at least 10%, at least 15%, or at least 20% by weight of the total weight of all polylactides. In some embodiments, polylactide (b) comprises up to 40%, up to 35%, or up to 30% of all polylactides.

[0056] Other polylactides may be present, but if present, may comprise no more than 10%, no more than 5%, no more than 2% of the total weight of the constituent polylactides, or may be absent.

[0057] The hydrolysis rate and mass loss rate of polylactide resin composition varies with the ratio of PMLA and polylactide (b).The higher the ratio of PMLA, the faster the hydrolysis and mass loss rate tends to be, and vice versa.Therefore, this ratio can be varied, thereby adjusting the hydrolysis and mass loss rate of the composition upwards and downwards.The higher the ratio of PMLA, the less residue tends to be.

[0058] The rate of hydrolysis and mass loss can be further enhanced by including in the polylactide resin composition an organic carboxylic acid having from 6 to 30 carbon atoms, particularly from 8 to 22 carbon atoms, and / or one or more anhydrides of such an acid. The organic carboxylic acid can have one, two or more carboxyl groups. Among suitable organic acids are straight chain alkanoic acids such as n-hexanoic acid, n-octanoic acid, n-decanoic acid, lauric acid, myristic acid, stearic acid, etc.; branched alkanoic acids such as 2-, 3-, and / or 4-methylvaleric acid, 2-hexyldecanoic acid, 2-butyloctanoic acid, 2-ethylhexanoic acid, 2-ethyloctanoic acid, 2-ethyldecanoic acid, and 2-ethylbutyric acid; mono- and / or polyunsaturated alkanoic acids such as 2-hexenoic acid, undecylenic acid, petroselinic acid, oleic acid, erucic acid, ricinoleic acid, linoleic acid, linolenic acid, etc.; aromatic substituted acids such as benzoic acid, hydrocinnamic acid, 4-isopropylbenzoic acid, and ibuprofen; and other aliphatic carboxylic acids such as monobutrin. In addition, any of the above substituted with one or more halogen and / or hydroxyl groups are suitable. Corresponding anhydrides of any one or more of the above are also useful. Preferred organic acids include linear or branched alkanoic acids having 8 to 18 carbon atoms, with lauric acid being particularly preferred.

[0059] If present, the amount of organic carboxylic acid can be 0.1-20% of the total weight of organic carboxylic acid plus all polylactides in the polylactide resin composition. The rate of hydrolysis and mass loss increases with increasing amount of acid. Thus, the amount of acid represents another variable by which the rate of hydrolysis and mass loss can be adjusted upwards and downwards. If present, the preferred amount of organic acid is at least 1% or at least 2% based on the above, and up to 12%, up to 10%, or up to 8%.

[0060] The polylactide resin composition may contain other materials to make it useful for the particular end use in which it will be used. These may include, for example, polymers other than polylactide, i.e., non-polylactide polymers. Such polymers may themselves be hydrolyzable and / or biodegradable. In such cases, such polymers may function, at least in part, to further modify the hydrolysis behavior or polylactide composition. One example of such a hydrolyzable polymer is polyglycolic acid, i.e., a polymer or copolymer of glycolide or glycolic acid, which, when present, may accelerate the hydrolysis and mass loss rate of the polylactide resin composition.

[0061] When present, the non-polylactide polymer may constitute, for example, 0.1 to 50%, 1 to 25%, or 1 to 10% of the combined amount of non-polylactide polymer and polylactide.

[0062] Other optional materials that may be present in the polylactide resin composition include crystallization nucleating agents such as finely divided solids, colorants, impact modifiers, internal and / or external lubricants, antiblocking agents, and extrusion processing aids, etc. The polylactide resin compositions of the present invention can be compounded with various types of reinforcing fillers or fibers to produce reinforced composite materials.

[0063] The polylactide resin composition can be foamed to reduce its density below the bulk density of the polylactide. This can be done, for example, by various extrusion processes in which a melt of polylactide is combined with a blowing agent under reduced pressure. The melt is then transferred to an area of ​​lower pressure so that the polylactide volatilizes as it cools, thereby foaming the composition. Other foaming methods can be used, such as various bubbling and beading methods. A solid blended polylactide resin composition can be produced with a fugitive material compound, followed by removal of the fugitive material to form voids in the composition. The reduced density can be at least 0.1 g / cm. 3 , at least 0.25 g / cm 3 , or at least 0.5 g / cm 3And, for example, 1.2 g / cm 3 Up to 1.1g / cm 3 Up to 1g / cm 3 or 0.9g / cm 3 The reduced density can impart buoyancy characteristics that are sometimes desirable.

[0064] The polylactide resin composition is useful in the same manner as conventional polylactide compositions, where little or low crystallinity is required. It can be melt processed by processes such as extrusion into pellets, extrusion foaming, blow molding, injection stretch blow molding, thermoforming, injection molding, melt spinning, lamination, and the like. It can be formed into various dispersions for coating applications. Of particular interest are applications in which it is desired that the polylactide resin composition hydrolyze, either during use or after use (such as at disposal). The fast rate of hydrolysis and mass loss exhibited by the polylactide resin composition of the present invention, especially at low to moderately elevated temperatures, such as 37-66°C, is an important advantage of the present invention.

[0065] The polylactide resin composition may be hydrolyzed by exposure to liquid water (or other aqueous solution) and / or steam. During hydrolysis, the polylactide resin composition may be, for example, immersed in or contacted with liquid water (or other aqueous solution) or may be contacted with steam. The temperature affects the rate of hydrolysis and mass loss, the higher the temperature the higher the rate. If overpressure is used to prevent the water from boiling or if hydrolysis is affected by steam pressure, the temperature may be, for example, above 0°C up to 100°C or even higher. In some embodiments, such as composting applications, the temperature may be, for example, 0-50°C. In other embodiments, the hydrolysis is carried out in the presence of liquid water at temperatures of 40-66°C, 48-66°C, or 48-60°C. These latter temperatures are specific to the particular oil and / or gas producing wells in which the polylactide resin compositions of the present invention are useful as diverters.

[0066] Due to the relatively fast mass transport of water to and within small particles, the polylactide compositions can be provided in small particulate form, such as pellets, beads, powders and fibers, or as thin articles. Such particles can be, for example, 1 cm 2 Less than 0.1cm 2 Less than or equal to 1mm 2 Thin articles may have a thickness (smallest dimension) of 2.54 mm or less, or 1 mm or less. For composting applications, larger articles may be ground, shredded, pulverized, or crushed to reduce the thickness or cross-sectional area to promote faster hydrolysis and mass loss.

[0067] When in particulate form, the polylactide resin compositions of the present invention, when hydrolyzed under certain temperature conditions, tend to exhibit an induction period during which hydrolysis occurs but little or no mass loss is observed because the hydrolysis products have not yet reached the low molecular weight <1000 g / mol required for solubility in the hydrolysis medium. The observation of an induction period is consistent with a bulk hydrolysis mechanism for PLA, where the rate of water diffusion exceeds the rate of ester hydrolysis.

[0068] This induction period may require several hours or days, depending on factors such as the temperature and composition of the polylactide resin, including the ratio of PMLA to polylactide (b) and the amount of organic acid, if any. The particles typically maintain their granular nature during this induction period.

[0069] This induction phase is accompanied by a period of relatively fast mass loss as hydrolysis proceeds to the point where low molecular weight hydrolysis products form and dissolve. As mass is lost during this period, the size of the particles decreases. In some cases, the particles may aggregate slightly, especially during the early stages of the mass loss period. The mass loss during this period may account for, for example, 50-95% of the total starting mass of the polylactide resin composition. In certain embodiments, at least 60%, at least 70%, at least 75%, at least 80%, or at least 85% of the starting mass is lost during this stage.

[0070] It has been found that the D-lactic acid content of the residual polylactide resin in the polylactide resin composition changes due to mass loss. In general, the proportion of the less predominant lactic acid unit enantiomer tends to decrease as hydrolysis proceeds and mass is lost. For example, if polylactide (b) contains primarily L-lactic acid units, the polylactide resin composition at the start of hydrolysis will also contain a small predominance of L-lactic acid units relative to D-lactic acid units. As mass is lost, the L-lactic acid units in the remaining material tend to become more and more predominant. Although the invention is not limited to any theory, it is believed that this may be at least in part due to the faster hydrolysis and mass loss of PMLA compared to polylactide (b).

[0071] Quite surprisingly, it has also been found that the remaining particles of the polylactide resin composition tend to develop a significant amount of crystallinity as they lose mass. Unusually, the degree of crystallinity that occurs can exceed the degree of crystallinity that can be obtained by crystallizing polylactide (b) alone. In some embodiments, polylactide (b) is unable to crystallize by itself, or is barely able to crystallize, and the polylactide composition of the present invention during the mass loss stage has been found to form a very significant amount of crystallinity, such as 20 J / g or more or 30 J / g or more of microcrystals. Without limiting the invention to any theory, it is believed that the crystallinity forms because the molecular weight of the remaining polylactide resin is reduced, forming oligomers that can easily crystallize, even if polylactide (b) crystallizes slowly or not at all prior to hydrolysis.

[0072] As the particles become more crystalline, the small amount of aggregation seen earlier tends to be lost and the particles tend to become free-flowing and non-agglomerated again.

[0073] After losing 50-95% of its initial mass, the mass of the polylactide resin composition tends to reach a plateau, where further mass loss occurs very slowly. This mass loss plateau may be due to the highly crystalline nature of the remaining composition, where hydrolysis proceeds very slowly. The crystallinity of the remaining mass of the polylactide resin composition at this point may be at least 40 J / g, at least 45 J / g, or 50 J / g or more. An advantage of the present invention is that this plateau is often not reached until at least 75%, at least 80%, at least 85%, or at least 90% of the mass of the starting polylactide resin composition has been lost. Correspondingly, the residue is often no more than 25%, no more than 20%, no more than 15%, or even no more than 10% of the starting weight of the polylactide resin composition. Given time and a sufficient concentration of water, these crystallites may further hydrolyze and eventually dissolve in the hydrolysis medium.

[0074] The mass loss behavior of two polylactide resin compositions, described more fully in the Examples section below, is illustrated in Figures 1 and 2.

[0075] The polylactide resin compositions of the present invention are typically resistant to dry blocking, i.e., blocking when heated in air in the absence of liquid water to temperatures of about 44° C. or greater, as determined using the test method described in the Examples below. The tendency to dry block can be reduced by applying a lubricant, such as ethylene bis(stearamide), various fatty acid esters, salts and amides, various silicone lubricants, to the surface of the polylactide resin composition particles. A convenient amount of such a lubricant is, for example, 100 to 10,000 parts by weight of lubricant per million parts by weight (ppm) of particles. Application of such a lubricant can increase the temperature at which the particles will resist dry blocking.

[0076] The polylactide resin composition of the present invention is particularly useful as a diverter in well treatment operations. In such operations, a granular polylactide resin composition is introduced into a well along with a treatment fluid. The particles can have a variety of sizes. The treatment fluid is usually aqueous. The treatment fluid generally takes the path of least resistance as it flows into a formation. The polylactide resin composition is carried along with the treatment fluid and fills the break, thus providing a physical barrier to further flow of the treatment fluid through the section in which the diverter is deposited. Thus, further flow of the treatment fluid is forced into less accessible areas of the formation. The primary reason for using a degradable diverter is to increase the stimulated reservoir volume of a given formation.

[0077] The diverter should remain in place temporarily so as not to block the recovery of hydrocarbons through those sections of the formation occupied by the diverter. Thus, the diverter is installed in the formation and simultaneously subjected to hydrolysis conditions by exposure to water, preferably elevated temperature. The elevated temperature can be, for example, 40-66°C, 48-66°C, or 48-60°C. The hydrolysis conditions can be maintained until at least 50%, at least 60%, at least 70%, at least 75%, at least 80%, or at least 85% of the starting mass of the polylactide resin composition has been lost due to hydrolysis. This can require, in some embodiments, for example, at least 1, at least 2, at least 5, at least 8, at least 10, or at least 14 days, depending on factors such as the particular polylactide resin composition and hydrolysis conditions (e.g., ratio of PMLA to polylactide (b), selection of polylactide (b), presence and amount of hydrolysis promoter, etc.).

[0078] In some embodiments, a diverter comprising a granular polylactide resin composition of the present invention has a t of 20 days or less, 15 days or less, 12 days or less, or 10 days or less when hydrolyzed by immersion of the particles in deionized water at a temperature of 130° F. in a sealed vial. 1 / 2(time to reach 50% mass loss). According to this test protocol, t 1 / 2 is preferably at least 1, at least 2, at least 5, or at least 8 days.

[0079] The following examples illustrate the invention but are not intended to be in any way limiting thereof. All parts and percentages are by weight unless otherwise specified.

[0080] PMLA1 is a linear copolymer produced by polymerizing a mixture of about 90% meso-lactide and 10% L-lactide at 160-180°C in the presence of a tin catalyst. The lactic units account for more than 98% of the total weight of PMLA1. 45% of the lactic units are D-lactic units and 55% are L-lactic units. PMLA1 has a number average molecular weight of 68,000 g / mol and a weight average molecular weight of 131,000 g / mol, as measured by GPC against polystyrene standards. PMLA1 has an average length of the blocks of L-lactic and D-lactic units of 1.1-1.75.

[0081] PMLA2 is a linear copolymer similar to PMLA1, except that it has a number average molecular weight of 31,000 g / mol and a weight average molecular weight of 75,000 g / mol, as measured by GPC against polystyrene standards. PMLA1 has an average length of 1.1-1.75 for the blocks of L- and D-lactic units.

[0082] Polylactide (b-1) is a linear random copolymer of about 76% L-lactide, about 1.5% D-lactide, and about 22.5% meso-lactide. Lactic units account for more than 98% of the total weight of polylactide (b-1). About 12% of the lactic units are D-lactic units and about 88% are L-lactic units. Polylactide (b-1) has a relative viscosity of 2.5. The relative viscosity is the ratio of the viscosity of a 1% (weight / volume) solution of polylactide resin in chloroform to a chloroform standard measured using a capillary viscometer at 30° C. Polylactide (b-1) is an amorphous grade that forms little or no crystallites when heated in air at 110° C. for several hours.

[0083] Polylactide (b-2) is a linear random copolymer of L-lactide, meso-lactide and a small amount of D-lactide. Lactic acid units account for more than 98% of the total weight of polylactide (b-2). Approximately 1.4% of the lactic acid units are D-lactic acid units and approximately 98.6% are L-lactic acid units. Polylactide (b-2) has a relative viscosity of 2.5. Polylactide (b-2) is a semi-crystalline grade that easily crystallizes when heated in air at 110° C. for several hours.

[0084] Mass loss experiments are performed according to the following protocol: 2 g of sample and 20 mL of deionized water are placed in each of several vials. The vials are sealed. The vials are then placed in a controlled temperature environment. Over time, one vial at a time is removed at regular intervals. Blocking / agglomeration is assessed by inverting the removed vial and checking for remaining solids. If the solids are not free-flowing, then the walls of the vial are tapped in an attempt to break up the agglomerates. The liquid phase is separated from the remaining solids by filtration, and the solids are then dried under vacuum at 40° C. for at least overnight, then weighed to determine mass loss. The point at which 50% of the starting mass is lost is designated t 1 / 2 The test is continued until the remaining mass reaches a plateau where there is little or no further mass loss. Measure the mass of the residue (the mass remaining upon reaching the plateau). EXAMPLES

[0085] Examples 1-2 and Comparative Samples A-C Blends of polylactide (b-1) and PMLA1 with lauric acid are prepared by melt blending the ingredients shown in Table 1 in a twin screw extruder and extruding strands of the resulting blend, which are then pelletized in water into 2.5 mm to 4.0 mm pellets. In each case, the ratio of polylactide (b-1):PMLA1 is 30 / 70 (by weight).

[0086] [Table 1]

[0087] Similarly, melt blends of polylactide (b-1) and lauric acid are prepared in ratios of 98:2 and 92:8 and formed into pellets. Blends of 0%, 2%, and 8% lauric acid with polylactide (b-1) are designated Comparative Samples A, B, and C, respectively.

[0088] Mass loss evaluation is performed in Example 1 at a temperature of 50° C. (122° F.). In addition to measuring mass loss, the remaining solids taken after various time points were evaluated for crystallinity and crystalline melting temperature by differential scanning calorimetry, lauric acid content by GC / FID, and % D-lactic acid enantiomer using a GC / FID method capable of separating the enantiomers of lactic acid derivatives. The results are illustrated in FIG.

[0089] As shown in Figure 1, the starting sample contains 34.7% D-lactic acid enantiomer (relative to all lactic acid units) (point A). It contains no crystallinity and therefore has no measurable melting temperature.

[0090] No weight loss is observed prior to day 6, and no significant changes in crystallinity or enantiomeric ratio are detected at that time point (point B). Mass loss appears to begin at about day 7. A period of relatively rapid mass loss follows, during which about 80% of the starting mass is lost over a period of about 28 days; 1 / 2 The average retention time is 15-16 days. As shown by points C, D, and E, the proportion of the D-lactic acid enantiomer steadily decreases over this time, dropping to only 9.2% after 24 days (point D). At that point, the remaining solid is highly crystalline and exhibits a melting temperature of 112 °C. The lauric acid concentration also increases during this period.

[0091] These results suggest that PMLA is preferentially hydrolyzed and lost from the sample during this period of relatively rapid mass loss. The large increase in crystallinity, especially between points D and E, also suggests that polylactide (b-1) is slowly hydrolyzing as well, even at room temperature. It is noted that the crystallinity that occurs early, as at point C, is significantly higher than would occur with polylactide (b-1) itself. As polylactide (b-1) hydrolyzes, it is believed to form oligomers that are highly enriched in the L-lactic acid enantiomer, as well as other oligomers that have significant proportions of both the L- and D-enantiomers. The oligomers formed are believed to readily crystallize, resulting in a large amount of crystallinity in the sample as hydrolysis proceeds. It is also believed that oligomers with lower enantiomeric purity are more likely to undergo further hydrolysis and dissolve in the aqueous phase, thereby resulting in mass loss.

[0092] Further mass loss slows after 28 days. As shown by points F and G, mass loss increases slightly from 80% to about 83% over the next 28 days. The ratio of D-lactic acid enantiomers in the residue continues to decrease, while the crystallinity and lauric acid content remain approximately constant. Thus, the residue of Example 1 is approximately 20%.

[0093] Example 2 and Comparative Samples A, B, and C are evaluated for mass loss at 50° C. in the same manner. 1 / 2 and residues (at the specified times) are shown in Table 2.

[0094] [Table 2]

[0095] The results in Table 2 demonstrate that not only does the inventive examples have a significantly increased hydrolysis rate, but also a significantly reduced residue, compared to comparative samples A-C.

[0096] Mass loss is determined at 54.4° C. for Example 2 and Comparative Samples A, B, and C, and at 60° C. for Example 2 and Comparative Samples B and C. The results are shown in Table 3.

[0097] [Table 3]

[0098] Similar results are seen at higher hydrolysis temperatures: the polylactide resin compositions of the present invention hydrolyze much more quickly and leave much less residue behind.

[0099] Examples 3 to 6 A melt blend of PMLA-1, polylactide (b-1) and lauric acid is prepared from the ingredients shown in Table 4 in the manner described in the above examples. Mass loss is evaluated at 54.4°C; 1 / 2 and the residues are reported in Table 4.

[0100] [Table 4]

[0101] Examples 3-6 each show a fast rate of mass loss and low residue.

[0102] Examples 7 and 8 Melt blends of PMLA-2, polylactide (b-1), and lauric acid are prepared from the ingredients shown in Table 5 in the manner described in the above examples. Mass loss is evaluated at 50°C; 1 / 2 and the residues are reported in Table 5.

[0103] [Table 5]

[0104] Examples 9 to 13 Using the method described above, polylactide resin compositions are prepared by melt blending the components shown in Table 6. The mass loss is determined for each of these examples using the procedure described above at a hydrolysis temperature of 54.4° C.; in each case, t 1 / 2 as reported in Table 6.

[0105] [Table 6]

[0106] A very fast rate of mass loss is again observed even though polylactide (b-2) is a semi-crystalline grade that is expected to hydrolyze slowly.

[0107] For Example 13, the remaining solids taken at various time points are evaluated for crystallinity and crystalline melting temperature as described for Example 1. The results are depicted graphically in FIG.

[0108] As shown in FIG. 2, the sample after 3 days of hydrolysis contains about 33% (relative to all lactic acid units) of D-lactic acid enantiomer (point A). No weight loss is observed. The sample contains 24.7 J / g of crystallinity due to the presence of semi-crystalline polylactide grade (polylactide (b-2)). The melting temperature is 147° C. Unlike Example 1, this sample shows that crystallinity easily occurs in the hydrolysis process.

[0109] Mass loss is observed beginning at about day 4. This is followed by a relatively rapid mass loss during which about 70% of the starting mass is lost over a period of about 22-24 days, t 1 / 2 is about 11 days. As shown by points B, C, D, and E, the proportion of D-lactic acid enantiomer steadily decreases over this time, dropping to only 1.5% after 22 days (point E). Crystallinity increases to 58 J / g after 22 days (point E).

[0110] Further mass loss after 22 days is slow. Mass loss increases slightly from 70% to about 75-78% over the next 48 days, as shown by points F and G. The proportion of D-lactic acid enantiomer in the residue continues to decrease, while the crystallinity remains approximately constant, as shown by points F and G. Thus, the residue of Example 2 is approximately 22-25%.

[0111] During the course of the mass loss experiment, Examples 11-13 are observed for blocking behavior. Example 11 remains free-flowing granular throughout the course of the mass loss experiment. Examples 12 and 13 form light agglomerates that break apart when tapped against the wall of the vial or gently stirred.

[0112] Examples 12 and 13 are evaluated for dry blocking. A small amount of pellets in each case is placed in a 50 mL polypropylene centrifuge tube. A metal cylinder is added to the top of the pellets in each tube to simulate a head pressure of about 1 psig (6.89 kPa). The tube assemblies defined above are heated in an oven for 24 hours at various temperatures, then the metal cylinder is removed and the pellets are examined for flow behavior after cooling to room temperature. If the pellets are not found to block, the tube assemblies are returned to the oven for another 24 hours, increasing the temperature in 2°C increments until the pellets are found to block.

[0113] Thus, when tested at 35° C., Example 12 remains a free-flowing granule. When tested at 40° C., light agglomerates form that are easily broken apart by tapping the outside of the vial. When 1000 ppm of ethylene bis(stearamide) (EBS) is applied to the particle surface, the particles remain free-flowing up to 44° C., and only light agglomerates form that are easily broken down at temperatures up to 50° C.

[0114] Example 13, untreated with EBS, is carried out similarly to Example 12. When 1000 ppm EBS is applied to the particle surface, the particles remain free-flowing up to 44° C. and form only light agglomerates at 46° C. that break down easily.

Claims

1. a) 50 to 95% by weight, based on the weight of all polylactides in the composition, of at least one polymer or copolymer of meso-lactide having a number average molecular weight of at least 5000 g / mol, as measured by gel permeation chromatography against polystyrene standards, said polymer or copolymer containing at least 90% by weight of lactic acid units, at least 80% of said lactic acid units being formed by polymerization of meso-lactide, and having an average length of the blocks of L- and D-lactic acid units of at least 1.1 to 2.0; b) 5 to 50% by weight, based on the weight of all polylactides in the composition, of at least one polylactide having a number average molecular weight, measured by gel permeation chromatography against polystyrene standards, of at least 5000 g / mol and containing at least 95% by weight of lactic units in a ratio of L-lactic to D-lactic units of ≧65:35 or ≦35:65; c) an organic carboxylic acid having 6 to 30 carbon atoms; 1. A polylactide resin composition comprising a melt or solution blend of

2. 2. The polylactide resin composition of claim 1, wherein component a) has a glass transition temperature of 38 to 50°C.

3. 3. The polylactide resin composition of claim 1 or 2, wherein component a) has an average length of the blocks of L-lactic and D-lactic units of at least 1.1 and up to 1.

75.

4. 4. The polylactide resin composition of claim 1, wherein the lactic acid units of component b) are L-lactic acid units and D-lactic acid units in a ratio of 75:25 to 100:0 or 0:100 to 25:

75.

5. 5. The polylactide resin composition of claim 1, wherein the lactic acid units of component b) are L-lactic acid units and D-lactic acid units in a ratio of 86:14 to 92:8 or 8:92 to 14:

86.

6. 6. The polylactide resin composition of claim 1, comprising 65 to 90% by weight of component a), based on the weight of all polylactides in the composition.

7. 7. The polylactide resin composition according to claim 1, wherein the organic carboxylic acid is a linear or branched alkanoic acid having 8 to 18 carbon atoms.

8. 8. The polylactide resin composition according to claim 1, comprising 2 to 12 weight percent of component c), based on the total weight of component c) and all polylactides in the polylactide resin composition.

9. 9. The polylactide resin composition of claim 1, further comprising a homopolymer or copolymer of glycolide or glycolic acid.

10. 10. The polylactide resin composition according to claim 9, comprising 0.1 to 50 weight percent of said homopolymer or copolymer of glycolide or glycolic acid, based on the total weight of said homopolymer or copolymer of glycolide or glycolic acid and all lactides in said polylactide resin composition.

11. 1. A method for treating underground formations, comprising: a) introducing into a subsurface formation a treatment fluid containing a liquid phase and particles of the polylactide composition of any one of claims 1 to 8, such that a mass of particles is deposited in the subsurface formation; and then b) hydrolyzing the deposited particles in the subsurface formation by exposing the deposited particles to an aqueous medium and elevated temperature such that the deposited particles lose at least 50% of their starting mass by hydrolysis; The method includes:

Citation Information

Patent Citations

  • Polylactic acid-based resin for pulverized toner, polylactic acid-based resin composition for pulverized toner, and pulverized toner using these

    JP2016050292A

  • Nail care agent

    JP2018020966A